The moderating influence of psychographics in homestay tourism in Malaysia - Nik Maheran Nik Muhammad; Salamiah A. Jamal; Nor' Ain Othman (2011)
Like other special interest tourism products, homestay as a community-based tourism product has shown substantial growth in terms of number of visits in recent years. Nevertheless, compared to other special interest tourism products, visitor behavior in homestay tourism has been neglected by the literature. This study fills this void by investigating the relationships between perceived value, satisfaction, and behavioral intention, and by examining the moderating influence of psychographics in a homestay tourism context. Respondents were visitors who visited selected homestay villages in Malaysia. Multi-group structural equation analysis was used to test for group differences in the structural weights.